Vessel Icing on the Shtokman FPSO - Efimov, Yaroslav (University of Stavanger, Norway, 2012)
Master's thesis in Offshore Technology The purpose of this report is to investigate the phenomenon of vessel icing in general and examine the problem for the Shtokman FPSO, which is now being designed to operate in severe conditions in the Barents Sea. Ice properties, icing conditions and intensity, geography of possible vessel icing are studied in details. Another aim is to develop theoretical models of the FPSO icing considering its dimensions and design features. The goal is to analyze all known anti – icing strategies, deicing and ice detection technologies for application and workability in the certain case of the Shtokman field. Finally possible affects of ice presence and icing on the FPSO productivity and stability are studied. The results of the work might be taken into account in further vessel’s design improvements and for efficient anti – icing strategies. One of several major features of the FPSO from icing point of view is sophisticated deck geometry with a number of deck structures of different height and width. Another issue is a presence of different equipment and engines that may act as sources of heat. This problem hasn’t been studied yet due to its specificity. The work combines both theoretical research basing on the new proposed mathematical model and numerical calculations of icing on the FPSO according to different international rules and standards. Results of this comparison are very promising and show potential for other work in this direction.